2013
DOI: 10.1371/journal.pone.0063231
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genetic Screening of KCNQ4 in a Large Autosomal Dominant Nonsyndromic Hearing Loss Cohort: Genotype-Phenotype Correlations and a Founder Mutation

Abstract: The present study of KCNQ4 mutations was carried out to 1) determine the prevalence by unbiased population-based genetic screening, 2) clarify the mutation spectrum and genotype/phenotype correlations, and 3) summarize clinical characteristics. In addition, a review of the reported mutations was performed for better understanding of this deafness gene. The screening using 287 probands from unbiased Japanese autosomal dominant nonsyndromic hearing loss (ADNSHL) families identified 19 families with 7 different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 17 publications
3
48
0
Order By: Relevance
“…20% x 25% = 5%). Our literature search also confirmed a maximum allelic heterogeneity of 5% in any given gene (Hildebrand et al, 2011;Iwasa, Nishio, & Usami, 2016;T. Naito et al, 2013).…”
Section: Dominant Hearing Losssupporting
confidence: 73%
“…20% x 25% = 5%). Our literature search also confirmed a maximum allelic heterogeneity of 5% in any given gene (Hildebrand et al, 2011;Iwasa, Nishio, & Usami, 2016;T. Naito et al, 2013).…”
Section: Dominant Hearing Losssupporting
confidence: 73%
“…Therefore, a total of 6 (8.0%) of the 75 patients were thought to have KCNQ4 mutations. KCNQ4 mutations are considered to be the most important causative mutation in Japanese ADSNHL patients, as we reported previously[18]. WFS1 and COCH gene mutations were also reported to be frequently identified causes of ADSNHL[25, 26].…”
Section: Discussionmentioning
confidence: 63%
“…As a result, we detected causative mutations in 5 patients. KCNQ4 mutations (c.211delC and c.229_230insGC) could not be detected by MPS because of technical limitations (extremely high GC contents), although this mutation was found frequently, as we previously reported[18]. We believe that the 2 nd screening step was particularly useful for detecting KCNQ4 mutations.…”
Section: Discussionmentioning
confidence: 74%
“…In their study, 19 families with 7 different mutations were identified in 287 probands from ADNSHL families [6]. Mutations of KCNQ4 were also found in other east Asian region, such as Korea and other Japanese population (Table 1).…”
Section: Discussionmentioning
confidence: 94%